2019
DOI: 10.1101/794578
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Thetaburst TMS to the posterior superior temporal sulcus decreases resting-state fMRI connectivity across the face processing network

Abstract: AbstractHumans process faces using a network of face-selective regions distributed across the brain. Neuropsychological patient studies demonstrate that focal damage to nodes in this network can impair face recognition, but such patients are rare. We approximated the effects of damage to the face network in neurologically normal human participants using thetaburst transcranial magnetic stimulation (TBS). Multi-echo functional magnetic resonance imaging (fMRI) resting-state data… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…The current chapter covers forty papers, demonstrating the growth of this area. Moreover, the past ten years have also seen studies that have combined TMS with EEG (Sadeh et al, 2011, Mattavelli et al, 2019 and TMS with fMRI (Pitcher, 2014, Pitcher et al, 2017, Handwerker et al, 2020 to study disruption across the extended face network. It is hoped that future TMS studies will continue to produce exciting and innovative insights into face processing in the coming years.221…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The current chapter covers forty papers, demonstrating the growth of this area. Moreover, the past ten years have also seen studies that have combined TMS with EEG (Sadeh et al, 2011, Mattavelli et al, 2019 and TMS with fMRI (Pitcher, 2014, Pitcher et al, 2017, Handwerker et al, 2020 to study disruption across the extended face network. It is hoped that future TMS studies will continue to produce exciting and innovative insights into face processing in the coming years.221…”
Section: Resultsmentioning
confidence: 99%
“…Neural activity can be measured across the face network using fMRI before and after lateral face-selective areas such as the OFA or pSTS are stimulated. The remote effects of this stimulation can then be measured in remote areas such as the FFA (Pitcher, 2014) and the amygdala (Pitcher et al, 2017, Handwerker et al, 2020.…”
Section: The Face Networkmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, recent work has explored this question with respect to the face-selective network using consecutive TMS/fMRI (Pitcher et al, 2014(Pitcher et al, , 2017Handwerker et al, 2020). Here, it was shown that TMS of the occipital face area (OFA; Gauthier et al, 2000) led to a local reduction in the response to faces within the OFA itself.…”
Section: Introductionmentioning
confidence: 99%